An investigation into linguistic features of sports expressions used metaphorically and idiomatically In non-sport situations (english versus vietnamese) (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Sport is an indispensable part of our daily life. In the domain of sport, the use of expressions used metaphorically and idiomatically is quite common, the metaphors and idioms either taking sports as a topic, or seeing it as a vehicle. This thesis focuses on the semantic and syntactic analysis of metaphors and idioms in sport expressions. This research aims to validate the sporting essence for vehicle selection and the use of metaphors and idioms taking sports as the vehicle in daily conversation. It discusses how the essence of sports influences metaphorical and idiomatic language, and thereby how culture can be observed through the analysis of metaphors and idioms. The results show that, first of all, due to the competitive nature of sport, the metaphors taking war as a vehicle constitute the main framework across different sports domains. Second, everyday conversation, the metaphors taking sports as the vehicle may vary usage depending on the different kinds of sports, that is; the use of sport metaphors involved, depends on the user’s familiarity with sport. Third, the link between the vehicle and the topic is usually created and enhanced by the life experiences and historical reality shared by the metaphor users, and it echoes the theory proposed by Lakoff and Johnson that human physical experience forms an important basis for the metaphorical extension, from concrete to abstract.